Reserve Currencies in an Evolving International Monetary System - Iancu, Alina (Departmental Papers; Departmental Paper ;, 2020)
Despite major structural shifts in the international monetary system over the past six decades, the US dollar remains the dominant international reserve currency. Using a newly compiled database of individual economies' reserve holdings by currency, this departmental paper finds that financial links have been an increasingly important driver of reserve currency configurations since the global financial crisis, particularly for emerging market and developing economies. The paper also finds a rise in inertial effects, implying that the US dollar dominance is likely to endure. But historical precedents of sudden changes suggest that new developments, such as the emergence of digital currencies and new payments ecosystems, could accelerate the transition to a new landscape of reserve currencies.